HEIP1 orchestrates pro-crossover protein activity during mammalian meiosis - Arnaud De Muyt; Sunkyung Lee; Sushil Khanal; Laurine Dal Toe; Céline Adam; Raphael Mercier; Valérie Borde; Neil Hunter; Thomas Robert (Proceedings of the National Academy of Sciences, 2025)
Meiotic crossovers (COs) are needed to produce genetically balanced gametes. In mammals, CO formation is mediated by a conserved set of pro-CO proteins via mechanisms that remain unclear. Here, we characterize a mammalian pro-CO factor HEIP1. In mouse HEIP1 is essential for crossover and fertility of both sexes. HEIP1 promotes crossover by orchestrating the recruitment of other pro-CO proteins, including the MutSγ complex (MSH4-MSH5) and E3 ligases (HEI10, RNF212, and RNF212B), that are required to mature CO sites and recruit the CO-specific resolution complex MutLγ. Moreover, HEIP1 directly interacts with HEI10, suggesting a direct role in controlling the recruitment of pro-CO E3 ligases. During early stages of meiotic prophase I, HEIP1 interacts with the chromosome axes, independently of recombination, before relocalizing to the central region of the synaptonemal complex. We propose that HEIP1 is a conserved master regulator of CO proteins that controls different CO maturation steps.